IL-33 Alleviated Brain Damage via Anti-apoptosis, Endoplasmic Reticulum Stress, and Inflammation After Epilepsy - Gao, Yuan; Luo, Chengliang; Yao, Yi; Huang, Junjie; Fu, Huifang; Xia, Chongjian; Ye, Guanghua; Yu, Linsheng; Han, Junge; Fan, Yanyan; Tao, Luyang (Frontiers in Neuroscience, 2020)
Interleukin (IL)-33 belongs to a novel chromatin-associated cytokine newly recognized by the IL-1 family, and its specific receptor is the orphan IL-1 receptor (ST2). Cumulative evidence suggests that IL-33 plays a crucial effect on the pathological changes and pathogenesis of central nervous system (CNS) diseases and injuries, such as recurrent neonatal seizures (RNS). However, the roles of IL-33and its related molecular mechanisms in RNS remain confused. In the present study, we investigated the protein expression changes and co-localized cell types of IL-33 or ST2L, as well as the effect of IL-33 on RNS-induced neurobehavioral defects, weight loss, and apoptosis. Moreover, an inhibitor of IL-33, anti-IL-33 was performed to further exploited underlying mechanisms. We found that administration of IL-33 up-regulated the expression levels of IL-33 and ST2L, and increased the number of its co-localization with Olig-2-positive oligodendrocytes and NeuN-positive neurons at 72 h post-RNS. Noteworthily, RNS-induced neurobehavioral deficits, body weight loss and spatial learning and memory impairment, as well as cell apoptosis, were reversed by IL-33 pretreatment. Additionally, the increase in IL-1β and TNF-α levels, up-regulation of ER stress, as well as a decrease in anti-apoptotic protein Bcl-2 and an increase in pro-apoptotic protein CC-3 induced by RNS are prevented by administration of IL-33. Moreover, anti-IL-33 treatment significantly inverted the effects of IL-33 mentioned above. Collectively, these data suggest that IL-33 attenuates RNS-induced neurobehavioral disorders, body weight loss and spatial learning and memory deficits, at least in part through mechanisms involved in inhibition of apoptosis, ER stress and neuro-inflammation.